(untitled) (American Journal of Multidisciplinary Research and Innovation, 2024)
The study examined the internet safety, cybersecurity and risks in technology environment. The study adopted a descriptive survey research design. The sample comprised 100 respondents drawn randomly online were used. College students cybersecurity awareness scale (r = 0.84) was used to collect data. Frequency counts and multiple regression analysis were used to analyse the data collected. 52 (52%) of the respondents are of age 16-20 years. Thirty-eight (38%) males responded while 62 (62%) are female and 89 (89%) maintain high levels of internet safety, and seventy-eight (78%) cybersecurity awareness. There is a linear relationship between predictor variables (internet safety and cybersecurity awareness) and risk in the technology environment r = 0.777. Internet safety (β = 0.823; t (98) = 10.816; p < .05) contributed most followed by cybersecurity awareness (β = 0.099; t (98) = 1.299; p < .05). It was deduced from the findings that there more users of high level of internet safety and cybersecurity awareness among college students. There is significant effect of internet safety and cybersecurity awareness on risk in technology environment. Although some of the internet safety measures are not well observed as they were considered not necessary. It is therefore recommended that all safety measures must be taken seriously by college students, as well as other technology users.